Development of Epigallocatechin and Ascorbic Acid Dual Delivery Transferosomes for Managing Alzheimer’s Disease: In Vitro and in Vivo Studies - Mishra G.; Awasthi R.; Mishra S.K.; Singh A.K.; Tiwari A.K.; Singh S.K.; Nandi M.K. (My University, 2025)
Epigallocatechin-3-gallate (EGCG) and ascorbic acid (AA)-loaded transferosomes (TRANS) were developed for brain delivery. The investigation covered EGCG-TRANS, AA-TRANS, and EGCG-AA-TRANS formulations using the film hydration technique. We analyzed the formed transferosomes to confirm the presence of vesicles loaded with the respective drugs and their performance within a living organism. The sizes of the particles for EGCG-TRANS, AA-TRANS, and EGCG-AA-TRANS were measured correspondingly at 174.2 ± 1.80, 132.7 ± 12.22, and 184.31 ± 9.5 nm. The appearance of diffused rings in the scanning electron microscopic image suggests that the payload has a crystalline structure. The atomic force microscope image displayed minimal surface irregularities, potentially indicating the presence of a lipid layer on the surface. Hemolysis results indicated the safety of the vesicles. The results showed 10.23, 7.21, and 8.20% of hemolysis for EGCG-TRANS, AA-TRANS, and EGCG-AA-TRANS, respectively. In the case of EGCG-AA-TRANS, the release of EGCG was determined to be 61.65% ± 4.61 after 72 h when exposed to phosphate buffer saline (pH 7.4). In vivo studies show a good response against Alzheimer’s disease (AD). EGCG-AA-TRANS (82.166%) exhibited a higher percentage of AChE inhibition in comparison to EGCG-TRANS (66.550%) and AA-TRANS (53.466%). Intranasal delivery of EGCG-AA-TRANS resulted in approximately a 5-fold enhancement in memory. Formulation allowed EGCG and AA to accumulate in various organs, including the brain. The results suggest that EGCG-AA-TRANS could be safe and effective for treating AD. © 2024 The Authors. Published by American Chemical Society.